Hubungan Jumlah Perenang dengan Sisa Klor di Kolam Renang Antasari Banjarbaru Tahun 2016 - Fadila Harariet; Darmiah Darmiah; Imam Santoso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: The relationship of total swimmers with residual chlorine in the swimming pool. The swimming pool as a means of public that usually visited by the people can potentially become vehicles for spreading germs through water contaminated media pool so that sanitation should always be considered. This study aims to determine the number of swimmers in the Swimming Pool Antasari Banjarbaru, determine residual chlorine in Swimming Pool. This type of research was analytic research with cross sectional approach. The population is all water swimming pool which used by swimmers and all swimmers in the pool by sampling as much as 5 spots, using correlation analysis. The results showed the number of swimmers on average were 151 swimmers with the lowest number were 113 swimmers and the highest were 223 swimmers. Residual chlorine inside the water of swimming pool was an average of 0.73 mg/L, the standard deviation was 0.71 mg/L with the lowest number was 0.01 mg/L and the highest number was 1.49 mg / L. The results of the analysis did not prove statistically no relationship with the rest of the swimmers amount of chlorine in Swimming Pool because H0 (p = 0.679> value α = 0.05) and the value of r was -0.218 so that the relationship can not be seen. Efforts to do so that residual chlorine water in Swimming Pool in accordance with the requirements is to conduct regular inspections both manager pool and the relevant agencies, maintain the quality of residual chlorine by adding chlorine stabilizer isocyanuric, and perform administration disinfection according to the dosage required to obtain results corresponding residual chlorine required pursuant Peraturan Menteri Kesehatan RI Nomor: 416/Menkes/Per/IX/1990. Keywords: Total swimmer; residual chlorine; swimming pool.